EP1183 Sebaceous carcinoma of the vulva: an unexpected diagnosis and review of the literature. (1st November 2019) - Rocha, A; Sá, MI; Abrantes, C; Raposo, S; Sousa, R; Correia, P; Aldinhas, P; Sá, L
Abstract : Introduction/Background: Sebaceous carcinoma(SC) of the vulva is a rare malignancy with potentially aggressive behavior of the sebaceous glands that is most commonly found in the periocular area. Nonetheless, there are sebaceous glands in the vulva and this diagnosis is especially rare with only nine previous cases described in the literature. Methodology: Case Report. Results: We report a case of a seventy-eight-year-old female patient who presented with vulvar pruritus, previously treated with topic steroids and antifungal, without improvement. The vulvar exam presented with a visible yellow papule which was biopsied and the microscopic examination revealed a sebaceous intra-epithelial carcinoma of the vulva in situ. We perform an excisional biopsy, uneventfully, with a posterior margin widening. One year after the diagnosis, she recurred with a lesion that was larger and in a multidisciplinary meeting it was decided that the patient should be submitted to a partial right vulvectomy with homolateral inguino-femoral sentinel node research (one node with was negative). Two weeks after the surgery, she presented a wound dehiscence in the groin area, re-sutured. The patient is without evidence of recurrence three months' post-surgery. Conclusion: In summary, SC of the vulva is rare variant of SC, that appears to have many clinicopathologic differences as compared to the classic disease. Our case reports the first one with an intra-epithelial component. It is important to recognize this tumor, with a microscopic evaluation and diagnosis, to report in detail any future cases towards a better understanding of the natural history of this disease. Disclosure: Nothing to disclose